Modern Theoretical Trends in Gender Studies - Kenjayeva Adolat Asrorovna (Goodwood Publishing, 2026)
Purpose: This article aims to examine modern theoretical trends in gender studies as an interdisciplinary field. Research Methodology: This study uses a literature-based approach by reviewing major contemporary perspectives in gender studies, including intersectionality, queer theory, trans studies, posthuman feminism, feminist new materialism, decolonial feminism, and digital gender studies. Results: The findings show that modern gender theory has shifted beyond binary male and female models toward broader analyses of power, discourse, embodiment, technology, race, class, sexuality, disability, and global inequality. Conclusions: Current gender studies increasingly emphasize relational, intersectional, and context-based analysis rather than fixed identity categories. Limitations: This study is limited to theoretical discussion and does not include empirical data or case-based analysis. Contributions: This study contributes to contemporary gender studies by mapping key theoretical developments and highlighting the shift toward more complex, intersectional, and contextual understandings of gender.